HUMAN RIGHTS PROTECTION IN CRIMINAL PROCEDURE: A SCIENTIFIC EXAMINATION - Komiljon Kizi, Abdusaidova Gulrukhsorabegim (International Journal of Business, Law and Political Science, 2024)
General Background: The protection of human rights within criminal procedure is essential for any justice system committed to upholding the rule of law and ensuring accountability. Specific Background: This article examines the fundamental principles of human rights in criminal procedures, highlighting how various legal frameworks—including international conventions and national laws—aim to safeguard individual rights amidst the complexities of law enforcement. Knowledge Gap: Despite the extensive discourse on human rights, there is a significant gap in understanding the practical implications and effectiveness of these protections within diverse criminal justice systems globally, particularly in balancing law enforcement with human dignity. Aims: This study aims to explore the core human rights principles relevant to criminal procedures and to analyze the challenges encountered in their implementation, with particular emphasis on due process, the right to a fair trial, protection from torture, and the presumption of innocence. Results: The findings reveal critical challenges in ensuring these protections, including systemic deficiencies, inadequate legal representation, and varying levels of commitment to international standards across jurisdictions. Novelty: By providing a comparative analysis of how different legal systems address human rights within criminal procedures, this research offers novel insights into effective practices and areas for reform. Implications: The implications of this study highlight the need for robust mechanisms to reinforce human rights protections in criminal justice, ultimately contributing to more equitable and just legal frameworks that uphold human dignity and public trust in the rule of law.